(untitled) (The Review of Diabetic Studies, 2025)
Cardiac arrest is one of the leading causes of mortality worldwide, and survival outcomes are highly dependent on the speed and quality of pre-hospital interventions. Emergency Medical Technicians (EMTs) play a vital role in the chain of survival, often serving as the first point of medical contact in out-of-hospital cardiac arrest (OHCA) cases. This review explores the impact of EMTs on time-critical interventions, including rapid recognition, initiation of cardiopulmonary resuscitation (CPR), defibrillation with automated external defibrillators (AEDs), airway management, and coordination with advanced emergency teams. Evidence indicates that EMT-led early interventions significantly improve return of spontaneous circulation (ROSC) and survival to hospital discharge. However, outcomes are influenced by several factors, such as EMS dispatch protocols, geographic disparities in response times, training variations, and availability of resources. Emerging technologies—including telemedicine, AI-assisted dispatch, and drone-delivered AEDs—offer promising avenues to enhance EMT effectiveness. Ethical and legal considerations, particularly related to scope of practice and decision-making in emergency contexts, further shape EMT contributions. This review concludes that strengthening EMT training, standardizing practices, and integrating innovative technologies are essential to optimize outcomes in cardiac arrest care and reduce global mortality.